An efficient two-stage user association scheme for green C-RAN systems - Ismail Hburi; H. F. Khazaal (Institute of Advanced Engineering and Science, 2019)
This paper addresses the energy efficiency (EE) based user-association problem in cloud radio-access network. In specific, a low-complexity 2-stage iterative algorithm is developed for this purpose by jointly employing the coordinated multi-point (CoMP) and user-clustering techniques. The first stage of the algorithm applies a greedy search to form user-cluster and activate corresponded remote radio heads (RRHs) for CoMP transmission, only an RRH j with good channel gain could be included in the serving cluster of user k. Next, in the second stage, a re-clustering procedure is utilized to mitigate inter-cluster interference (ICI) and assign optimal power for scheduled users. Our obtained findings confirm that the transmit power, RRH density, and the number of users served by these RRHs can significantly affect the EE. Also, the results show that under certain system settings the proposed scheme can enhance the EE by almost 39.6% compared to conventional CoMP without user clustering technique.